Combination of Chlorella vulgaris and Eichhornia crassipes for wastewater nitrogen removal - Bich, Nguyen Ngoc; Yaziz, Mohammad Ismail; Bakti, Nordin Abdul Kadir (Elsevier Science, 1999)
Waterhyacinth (Eichhornia crassipes) was introduced into a high rate algal pond (HRAP), in which the green alga Chlorella vulgaris was the dominant species. Twenty batch runs, each lasting 20 days, were conducted to treat raw rubber wastewater with a COD of about 500 mg/l. In this glasshouse experiment, the combined algae -waterhyacinth system removed 23% more nitrogen than did the normal HRAP, whilst suspended solids in the wastewater treated by the combined system was less than 50 mg/l.; Waterhyacinth (Eichhornia crassipes) was introduced into a high rate algal pond (HRAP), in which the green alga Chlorella vulgaris was the dominant species. Twenty batch runs, each lasting 20 days, were conducted to treat raw rubber wastewater with a COD of about 500 mg/l. In this glasshouse experiment, the combined algae-waterhyacinth system removed 23% more nitrogen than did the normal HRAP, whilst suspended solids in the wastewater treated by the combined system was less than 50 mg/l.